Advancing Self-Efficacy and Intuitive Decision-Making Calls to Action - Barry B. Leslie; Jon Moilanen (Adult Education Research Conference, 2010)
The purpose of this paper is to gain a better understanding of the connection between self-efficacy and intuitive calls to action as it relates to adult learners and adult learning contexts.